Controlling Effect of Wave-Dominated Delta Sedimentary Facies on Unconventional Reservoirs: A Case Study of Pinghu Tectonic Belt in Xihu Sag, East China Sea Basin. (13th June 2022) - Chen, Qinglong; Pu, Renhai; Xue, Xiaomin; Han, Ming; Wang, Yanxin; Cheng, Xin; Wu, Hanning
Abstract : In order to find the "sweet spots" of unconventional oil and gas from the Pinghu Formation in the Pinghu Tectonic Belt, we are committed to clarifying the development and distribution rules of coal-measure source rocks and tight reservoirs as well as the controlling factors. Using 3D seismic and logging data, combined with logging constraints of target lithology and pyrolysis experiments of source rock, "source and reservoir" research of uncoventional oil and gas was carried out in the Pinghu Tectonic Belt. The results show that two stages of regression and one stage of transgression occurred in the Pinghu Formation, resulting in river-controlled and wave-controlled delta-neritic facies dominated by sedimentary facies, source rocks developed in interdistributary bay and swamp microfacies, and tight sandstones in point bar and distributary channel microfacies are developed. The accumulation of coalbed methane and shale gas is controlled by the sedimentary facies and the degree of thermal evolution under the factors of burial depth. The accumulation of tight sandstone is closely related to the dominantly sedimentary facies and diagenetic modification of physical properties and faults. It is concluded that the structural type, type and distribution of faults, and depositional environment of the Pinghu Tectonic Belt in the Xihu Sag are the key factors controlling the development and accumulation of coal-measure source rocks and tight sandstone reservoirs. This understanding provides a clear direction for the deep exploration of unconventional oil and gas in the sag and provides a reference for finding reservoir "sweet spots."